Developing a Framework for a Collaborative Public Health Knowledge Translation Project: The SiREN Experience - Rochelle Tobin; Gemma Crawford; Justine E. Leavy; Jonathan Hallett; Roanna Lobo (Systems, 2026)
Knowledge translation (KT) involves the co-creation, exchange and dissemination of knowledge to increase evidence-informed public health. Increasingly, there is a demand to strengthen evidence-informed public health, and with this, a need to understand how to support KT efforts within public health systems. Whilst a variety of KT frameworks have been developed, frameworks and studies that provide insight into KT initiatives that operate across the individual, organisational and system levels are lacking. This paper presents the development of a KT framework used by a government-funded sexual health and blood-borne virus capacity-building partnership for research and evaluation in an Australian jurisdiction. The approaches taken and practical insights into operationalising a collaborative approach to KT are described. The process of developing the framework included inputs from the literature, a needs assessment survey, and stakeholder consultation. The final framework is composed of a conceptual model and a suite of KT strategies that reflect the dynamic and complex nature of KT in public health. The framework illustrates the broader influences of KT, key strategies, and guiding principles. Findings have relevance for service providers, researchers and policymakers (including funders) seeking ways to engage in KT at the individual, organisational and system levels.